12.2 HUMANISM AND SOCIAL JUSTICE IN THE POETIC VISION OF ZULFIYA - Sobirova A.J., Nasrillayeva G. J. Tashkent State Medical University (Innovative technologies in construction Scientific Journal, 2025)
This article examines the manifestation of humanism and social justice in the poetic worldview of Zulfiya Isroilova, one of the most influential voices in twentieth-century Uzbek literature. Her lyrical works represent a rare synthesis of emotional sincerity and moral strength, where poetry becomes both a mirror and a tool of ethical transformation. Zulfiya’s verses reflect the universal struggle for dignity, equality, and compassion — values that transcend time, gender, and nationality.Through her poetic language, Zulfiya created a spiritual space where humanity, fairness, and empathy form the foundation of moral consciousness. She saw poetry not merely as an aesthetic endeavor but as a moral responsibility — a way to give voice to the voiceless and to celebrate the sanctity of human life. Her poetic world consistently advocates for social harmony, condemns injustice, and elevates the inner beauty of the human spirit. The article explores how Zulfiya’s humanistic philosophy intertwines with her advocacy for women’s rights, education, and social progress. Her poems portray the individual as a bearer of collective responsibility and moral light. In the broader context of Uzbek literature, Zulfiya’s creative vision stands as an enduring symbol of moral courage and artistic sincerity — a legacy that continues to inspire readers to seek truth, empathy, and justice.